A twelve-month field study of the West African Thrush Turdus pelios (Passeriformes: Muscicapidae). Part 2: annual cycles - Akinpelu, Akinsola I (2005)
In Africa, birds inhabiting forested regions are less seasonal in their activities than those from openareas. In order to study annual cycles in forest regions of South western Nigeria, West African Thrushes (Turduspelios) were mist-netted and banded during the last two weeks of each month. The nest is a cup-shaped structurebuilt out of grasses, herbs, weeds, roots and earth laid out in a clockwise manner. Only the nesting tree and feedingsites were defended during the breeding period. The clutch size was 2.69 ± 0.20 eggs with a mean incubationperiod of 14.11 ± 0.26 days. The mean nestling period was 15 ± 1.00 days. The nestlings were fed on a variety ofplant and animal matter, of which grass seeds and insects were predominant. Moult was found to be protractedwith a population moult period of 194 days and a much shorter individual moult period. Moult and breedingperiods were spread out: moult period dovetailed into the breeding period. The birds were found to gain weightduring the period but they attained their maximum weight in August after the moult period. The lowest weightwas recorded in February, during the peak of the dry season, when food availability was lower.